A systematic literature review: What is the current stance towards weight stigmatization in social media platforms?. Issue 135 (March 2020) - Wanniarachchi, Vajisha Udayangi; Mathrani, Anuradha; Susnjak, Teo; Scogings, Chris
Highlights: Weight stigma results from negativity towards overweight individuals. Anonymity of social media has led to widespread weight stigmatization. Weight stigma correlates with psychological, social and biological themes. Psychological correlates are more frequently identified with weight stigma. Few weight stigma studies conducted using large social media text corpus. Abstract: Sensitivity of public discourses over social media platforms has been largely discussed in the recent past and considered one of the reasons that have led to widespread weight stigmatization. This article examines existing work on the biological, psychological and sociological consequences of weight stigmatization resulting from online conversations over social media. Articles were identified through EBSCO Discovery Service. Independent extraction of articles was conducted using predefined search data fields to synthesize prior works on biological, psychological and sociological correlates of weight stigma. Our findings have revealed psychological correlates to be most frequently identified with weight stigma than with biological and sociological correlates. Some correlations with gender and ethnicity have also been identified in previous studies; however, these studies are limited in their data acquisition and in use of analytic techniques. While there is widespread social media attention on the increasing overweight and obese population, the current research on weight stigmatization and interventions to tackle online stigmatization are not yet properly elucidated.